EVOLUTION OF THE ECONOMIC AND TECHNICAL INDICATORS FOR HOPS CULTURE IN ROMANIA. A RETROSPECTIVE OF THE LAST DECADE, 2006-2016 - Elena ȘURCĂ (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Hops is an increasingly rare crop on the territory of Romania, but this culture deserves attention due to its use. It is worth mentioning that the Romanian farmers are encouraged to cultivate this plant by increasing subsidies from one year to the next. For the analysis of evolution of this crop for the studied period, the technical indicators represented by the areas and production environments as well as the economic indicators represented by the prices, subsidies granted / ha and commercial trade will be taken into account. This paper seeks to highlight the technical and economic aspects presented above, their dynamics and the importance of this culture that will reflect on the demand for the national market for this product. The outcome of the study will highlight the support of the domestic hop market through domestic or imported production.